Diversity of endophytic bacteria in two banana cultivars and their potential for plant growth promoter - TRIASTUTI RAHAYU; YEKTI ASIH PURWESTRI; SITI SUBANDIYAH; YASIR SIDIQ; DONNY WIDIANTO (Society for Indonesian Biodiversity, 2024)
Abstract. Rahayu T, Purwestri YA, Subandiyah S, Sidiq Y, Widianto D. 2024. Diversity of endophytic bacteria in two banana cultivars and their potential for plant growth promoter. Biodiversitas 25: 2828-2838. The Klutuk banana plant (Musa balbisiana colla) is recognized as a resistant plant against biotic and abiotic stresses. The resistance trait of the cultivar is not exactly revealed but is most likely related to the presence of endophytic bacteria. This study aimed to determine the variation of banana cultivars and their organs on endophytic bacterial populations and their character as plant growth promoters (PGP). The study involved isolating endophytic bacteria from the root, corm, and petiole of cv. Klutuk and cv. Ambon, aged 4-5 months. Isolated endophytic bacteria were evaluated based on plant-growth-promoting (PGP) criteria. Subsequently, 16S rRNA sequences were amplified using 16S primers, 27f and 1492r, then sequenced. The obtained isolates were also identified by comparing the 16S sequences to the NCBI gene bank. The results showed that the population and number of isolates with the most PGP characters were in both banana cultivars' roots, petiole, and corm. Endophytic bacteria with multiple traits as PGP are composed of Phylum Proteobacteria (gamma, alpha, beta), Firmicutes, and Actinobacteria members. Several species are potential as they have multiple PGP traits with high-quantity test results, namely Microbacterium testaceum DSM 20166 strain, Simplicispira sp. CPCC 100842 strain, Klebsiella grimontii SB73 strain, Enterobacter mori LMG 25706 strain, Pantoea sp. CoA11 strain, Agrobacterium tumefaciens IAM 12048, Variovorax guangxiensis GXGD002 strain, Serratia nematodiphila DZ0503SBS1 strain, Bosea thiooxidans BI-42 strain, Erwinia tasmaniensis Et1/99 strain, Methylobacterium fujisawaense DSM 5686 strain, K2 isolate, K8 isolate, and K18 isolates. This study also revealed the endophytic bacterial population and character as plant organs influenced PGP. The roots and petioles became the banana plant organs colonized by endophytic bacteria with multiple traits as PGP. Overall, several isolates were discovered in cv. Klutuk were suspected of being new species with potential as PGP agents, and these were not identified in cv. Ambon.